Respuesta :

Answer: no solution

Step-by-step explanation:

First lets simplify

-2(x+3) + 2(x+4) = 24

-2x - 6 + 2x + 8 = 24

We can simplify this further by combining like terms

2=24 is the equation we get after combining like terms.

Since 2 is not equal to 24, the answer is no solution.

gmany

Answer:

NO SOLUTION

Step-by-step explanation:

[tex]-2(x+3)+2(x+4)=24\qquad\text{use the distributive property}\ a(b+c)=ab+ac\\\\(-2)(x)+(-2)(3)+(2)(x)+(2)(4)=24\\\\-2x-6+2x+8=24\qquad\text{combine like terms}\\\\(-2x+2x)+(-6+8)=24\\\\0+2=24\\\\2=24\qquad\bold{FALSE}\\\\\text{Conclusion:}\\\\\bold{NO\ SOLUTION}[/tex]